Key technologies for exploration and geological evaluation of deep carbon storage spaces - Wenping LI; Danping CAO; Wei QIAO; Zhengwu ZHOU; Qingliang CHANG; Songhang ZHANG; Shuangxing LIU; Yi SHEN; Wanjun LI; Xin FU; Bo LIU; Yan WANG; et al. (Meitan xuebao)
Driven by global climate change and the “dual carbon” goals, the efficient development and safe storage of deep carbon storage spaces have emerged as a critical pathway to achieve carbon neutrality. This paper systematically reviews the exploration technologies, site suitability evaluation methods, and key theoretical challenges for large-scale carbon storage in deep saline aquifers, depleted oil and gas reservoirs, unminable coal seams, and basalt formations. The study reveals that multiphysical field coupling effects (thermal-fluid-mechanical-chemical) induced by CO2 injection may trigger risks such as fault activation, caprock leakage, and seismic activity, necessitating the construction of a risk assessment framework through multiphysical field numerical simulation and dynamic monitoring. Deep saline aquifers account for 98.64% of China’s theoretical carbon storage potential, but their significant heterogeneity requires suitability evaluation that integrates geological stability (fault development, caprock sealing capacity) and storage capacity (porosity, permeability) to construct a multi-scale index system. Methods such as the analytic hierarchy process (AHP), GIS, and machine learning are combined to optimize site selection decisions. To address the complexity of deep carbon storage spaces, integrated seismic and electrical exploration technologies significantly improve reservoir identification accuracy: full-waveform inversion (FWI) characterizes pore-fracture structures, gravity-magnetic inversion constructs deep structural models, and multiphysical data fusion reduces the non-uniqueness of inversion results. In the context of green transformation in coal mines, the innovative “negative carbon backfilling” technology is proposed: CO2 is used to mineralize industrial solid wastes such as steel slag and fly ash to prepare backfilling materials, achieving high carbon sequestration rates while balancing ecological restoration and dynamic disaster prevention. The synergistic effect of CO2 storage in deep unminable coal seams and enhanced coalbed methane (ECBM) recovery is significant, requiring optimization of the full-life-cycle management model for “fracturing-displacement-storage”. CO2 storage in goafs faces challenges from the complex seepage-adsorption mechanisms in fractured coal-rock masses, necessitating the development of multiphase dynamic models to assess storage potential in free, adsorbed, and dissolved states. Potential calculation methods vary significantly by reservoir type: Saline aquifers use the storage mechanism method (coupling structural trapping, dissolution, and mineralization), depleted oil and gas reservoirs combine material balance methods with numerical simulation, and coal seams rely on adsorption capacity and displacement efficiency evaluations. In terms of injection technology innovation, micro-nano bubble injection enhances CO2 dissolution rates, while the “water-mixed dissolved-state injection” mode in basalt formations achieves high mineralization rates. Future research must emphasize interdisciplinary integration: Developing intelligent multiphysical field exploration and fine imaging to overcome challenges in detailed characterization of multi-type three-dimensional carbon storage spaces; researching and developing high-efficiency deep negative carbon backfilling materials and technical equipment; and constructing a comprehensive system for calculating CO2 storage potential and evaluating suitability in deep integrated three-dimensional spaces, form technical standard systems and information decision-making platforms, and provide theoretical and engineering support for large-scale geological storage under the “dual carbon”goals.